2001
DOI: 10.1007/s11661-001-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the mechanical effects induced by the tungsten inert-gas welding of the IN718 superalloy

Abstract: The distortion and residual stresses arising during the tungsten inert-gas (TIG) welding of the nickelbased superalloy IN718 are modeled using sequentially coupled thermal-mechanical analyses. Processing trials have been carried out for validation purposes, and, for a number of rectilinear testpieces, the distortion has been quantified. The residual stresses in one of the welds have been characterized using the neutron diffraction technique. For the same weld, the thermal cycles induced in the heataffected zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 10 publications
2
59
0
Order By: Relevance
“…Convergence studies have shown [4,20,21] that four elements through the thickness of the 4 mm plate, as modelled here, enable the distortions to be predicted accurately and efficiently.…”
Section: Finite Element Meshesmentioning
confidence: 91%
See 2 more Smart Citations
“…Convergence studies have shown [4,20,21] that four elements through the thickness of the 4 mm plate, as modelled here, enable the distortions to be predicted accurately and efficiently.…”
Section: Finite Element Meshesmentioning
confidence: 91%
“…The filler metal addition has not been modelled explicitly by, e.g. element rebirth or using a lumped enthalpy term during solidification as such effects are incorporated into the heat source term, as in [4,24,29]. The enthalpy change during the solid state phase transformation is modelled, Figure 6b, although rate effects on cooling are ignored.…”
Section: Thermal-mechanical Materials Properties and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature-dependent material properties were used, and heat loss on the surface by convection and radiation was considered. The thermal modeling results were calibrated by weld cross-section shape fit [7] corresponding to the weld geometry.…”
Section: Fig 2 Shape Of the Back (A) And Front (B) Side Of The Weldmentioning
confidence: 99%
“…However, such models demand knowledge of the temperature dependence of the thermophysical and mechanical properties of the material along with the distribution and magnitude of heat input into the material. Obtaining these data is again usually time-consuming and expensive, but has been performed in very many successful weld models in a range of materials, for example in the welding of steels [5,20], aluminium [19] and nickel [7,21] alloys.…”
Section: Introductionmentioning
confidence: 99%